Painting under different lighting conditions creates different color effects on the human figure - De los Santos, Jaime David 1948- (2002)
The study attempts to investigate how different lightning conditions affect color effects in painting. To be aware of light, its properties and behavior, serves as a solid guide for the artist to represent nature in canvas as close to reality. Eight painting demonstrations, done under different lightning conditions, illustrate the relationship of light and color, especially in color choices such as the use of secondary colors and primary colors, light and shadow such as the use of black and white, their brightness and dullness, and atmospheric and mood effects. The study contributes to working approach in painting, which may be called the "designing with light" approach. Color theories learned from academic training assume fixed values. It is through actual experience that the use of colors must be based on.
Vita.
Thesis (M. Fine Arts)--University of the Philippines, Diliman.
Keywords: Human figure in art; Painting -- Lighting